Effects of Government Expenditure on Foreign Exchange Reserves: Evidence for Namibia - Manuel, Victoria; Mbazima-Lando, Daisy; Naimhwaka, Erwin (International Journal of Economics and Financial Issues, 2023)
The study empirically investigated the effects of government expenditure on FX reserves in Namibia. Using quarterly data, the study applied the Autoregressive Distributed Lag (ARDL) cointegration technique to examine the relationship between FX reserves and government expenditure, the exchange rate, external borrowing, current account balance and M2 over the period ranging from 2002 to 2020. The results show that an increase in government expenditure reduces FX reserves. Furthermore, increase in foreign debt, current account balance and M2 increases the level of FX reserves, while an appreciation of the effective exchange rate reduces FX reserves. The study, therefore, concludes that high government expenditure and increase in foreign borrowing impacts FX reserves. These findings suggest that developments in government expenditure may hinder monetary policy effectiveness. Based on these findings, the study recommends the continuation of fiscal consolidation to reduce fiscal deficits and government debt. Similarly, it is important to ensure macroeconomic balance and appropriate coordination between fiscal and monetary policies.